2021
DOI: 10.1088/1748-9326/ac0e64
|View full text |Cite
|
Sign up to set email alerts
|

Exploring carbon footprint reduction pathways through urban lifestyle changes: a practical approach applied to Japanese cities

Abstract: Cities and urban consumers play a central role in the transition to a decarbonized society. Building on existing studies that identify the significant contributions of lifestyle changes, this study proposes a practical methodology for modeling and exploring city-specific carbon footprint reduction pathways through lifestyle changes to decarbonization. It uses an input–output approach with mixed-unit consumption data and the concept of adoption rates, which is applicable to multiple cities with widely available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…We also chose the target levels to comply with our footprints' scope. The scope differences are the main reason why average per capita footprints in our sample are lower than those reported in previous studies in the Nordics: 12.2 to 15.2 t CO 2 e in Denmark (Hertwich, Peters 2009, Ivanova et al 2016, 8.88 to 18 t CO 2 e in Finland (Hertwich, Peters 2009, Ala-Mantila et al 2016, Ivanova et al 2016, Salo and Nissinen 2017, Koide et al 2021a, 10.4 t CO 2 e in Iceland (Clarke et al 2017), 10.3 to 14.9 t CO 2 e in Norway and 8.7 to 10.5 t CO 2 e for Sweden (Hertwich, Peters 2009, Ivanova et al 2016. Other reasons include the changes in carbon intensities and consumption patterns since the other studies were conducted, as well as potentially higher adoption rates of the demand-side actions in our sample than in whole societies.…”
Section: Limitations and Uncertaintiescontrasting
confidence: 74%
See 2 more Smart Citations
“…We also chose the target levels to comply with our footprints' scope. The scope differences are the main reason why average per capita footprints in our sample are lower than those reported in previous studies in the Nordics: 12.2 to 15.2 t CO 2 e in Denmark (Hertwich, Peters 2009, Ivanova et al 2016, 8.88 to 18 t CO 2 e in Finland (Hertwich, Peters 2009, Ala-Mantila et al 2016, Ivanova et al 2016, Salo and Nissinen 2017, Koide et al 2021a, 10.4 t CO 2 e in Iceland (Clarke et al 2017), 10.3 to 14.9 t CO 2 e in Norway and 8.7 to 10.5 t CO 2 e for Sweden (Hertwich, Peters 2009, Ivanova et al 2016. Other reasons include the changes in carbon intensities and consumption patterns since the other studies were conducted, as well as potentially higher adoption rates of the demand-side actions in our sample than in whole societies.…”
Section: Limitations and Uncertaintiescontrasting
confidence: 74%
“…We also highlight that it takes multiple behavior changes to bring a personal carbon footprint to the target levels. Other research in affluent countries has reached the same conclusion, adding that high adoption rates are necessary to reach the targets at societal scales (Akenji et al 2021, Koide et al 2021a.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…On this basis, the household sector concurrently holds a crucial bearing on achieving emission reduction objectives and has considerable mitigation potential 47 , 48 . Evidence has demonstrated that seemingly trivial day-to-day actions, such as reducing water usage, turning off lights when not in use, and proper waste disposal, carry weight 49 – 52 . Therefore, this dataset focuses on the carbon footprint of Japan’s households, aiming to contribute to the body of knowledge that guides emission reduction strategies from the household perspective.…”
Section: Background and Summarymentioning
confidence: 99%
“…Brand et al (2020) highlight this in improved road safety and transport equality from the uptake of shared and multi-modal mobility, Costa et al emphasise the reduced pressure on natural resources, and Garvey et al (2021) the public health benefits of low-carbon dietary transitions. Multiple studies (Koide et al, 2021;Wiest et al, 2022) also addressed the feasibility of bringing about such change. The former showed that the needed uptake of behavioural changes to meet net-zero ranged from 62% to 87% of the population in a study covering 52 Japanese cities, while the later concede that it is unrealistic for all European citizens to adopt their proposed lifestyle changes.…”
Section: Behavioural Transitionsmentioning
confidence: 99%